»Potrebujemo več prakse!« Kako bodoče učiteljice in učitelji nemščine vrednotijo svoje izkušnje z mikropoučevanjem? - Retelj, Andreja; Kosevski Puljić, Brigita (Revija za elementarno izobraževanje, 2016)
“We Need more Practice!” How Future Teachers Evaluate Their Experiences with Micro-Teaching? This paper deals with micro-teaching as a possibility for combining theory and practice during the studies of future teachers of German. One of the key elements for combining theory and practice is pedagogical practicums in primary and secondary schools. From students’ reflections on their practicums, we have seen that it is very difficult for students to put their theoretical knowledge into practice. In order to alleviate initial difficulties and the anxiety future teachers face, we have implemented a specific micro-teaching model at the Department of German, Dutch and Swedish; students in the second year of the MA-level pedagogical stream participated in the model. The students’ self-evaluation on the effects of micro-learning showed it to be a useful model for obtaining their first pedagogical experience because it allows students, through reflection and feedback from their didactics teachers and from their fellow students, to become aware of the didactic and methodological principles of modern foreign language teaching and thus to be better prepared for their teaching practicums.
Keywords: micro-teaching; reflection; feedback; teaching